Simulación numérica de una prueba de reología capilar para un polímero PC+ABS (2021)
The aim of this work was to simulate the capillary rheometry test in the Fluent module of the ANSYS Workbech® interface. It was used a series of viscosity data obtained from a capillary rheometry test for a PC + ABS polymer. These data were corrected according to the non-Newtonian behavior of the polymer. The viscosity data was fitted to the Cross model by the Autodesk® Data Fitting application. The test parameters as geometry, temperature, and the speed of the rheometer piston were used to generate the numerical model in ANSYS Fluent® software. For the numerical model, the geometry was generated, and the boundary conditions were defined. For the geometry, an axisymmetric model was defined. The mesh was generated with a concentration of elements near the walls. When the program finished solving the model, the solution was analyzed. It was compared the pressure value from simulation with the pressure value from the physical test, and a correlation coefficient of 0.999 was obtained.